Marginalisation and power politics in local governance: a study of a small town in India. Issue 2 (17th February 2021) - Ghosh, Subhamay; Das, Dipendra Nath
ABSTRACT: This article uses an urban case from West Bengal, India, to reveal that people lacking socio-economic and cultural capital have marginal access to civic services provided by the municipality. This marginalisation is a product of the municipality's highly inequitable approach to governance practices, where there is a deliberate aversion to government schemes, infrastructure, and developmental projects aimed at marginal groups. Almost three decades after decentralisation, the town provides no platforms for citizens to participate in local governance mechanisms, and there are no NGOs and community-based organisations present in local governance. As there is no one to voice the concerns of marginalised groups, a gradual trend of marginalisation continues to occur.